Time for awareness of centile charts for anthropometry in Indian neonates: need of the hour? - J., Thinesh Kumar; E., Narayanan; Seeralar T., Arasar (International Journal of Contemporary Pediatrics, 2018)
Background: There is overestimation and underestimation of babies, the consequence being many AGA neonates labeled as SGA, and LGA neonates being overlooked and misinterpreted by using western based growth charts. So there is necessity to design Indian based growth charts for our babies. The objective is to construct gestational age and sex specific centile charts approximately for birth weight, length and head circumference for neonates born between 33 - 42 weeks of gestation and to compare with the other western growth charts. Methods: All babies were delivered in Institute of Obstetrics and Gynecology and nomograms for birth weight, head circumference and length of neonates were noted in time period between July 2016 and June 2017. Gestational age and sex specific smoothened centile curves were created for both sexes separately by Lamda Mu Sigma (LMS) method. Our new centile charts were compared with standard western growth charts. Results: Gestational age and sex specific raw and smoothened curves for birth weight, length and head circumference centiles were created from 8100 (4026 males, 4074 females) neonates. Female neonates were lighter than the male neonates. Birth weights of our Indian babies were lower with no change in length and head circumference centiles across all gestations. Conclusions: The growth charts designed in our study can be used as wide reference charts for birth weight, height and head circumference for Indian ethnic neonates for stratification of neonates into SGA, AGA and LGA unlike western charts, which extrapolates or misclassifies our neonates thereby minimizing unnecessary interventions and complications.